The Expert Control Designing of Tanker Ship Maneuvering by Optimal Control as a Reference Model - Aulia S. Aisjah (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2009)
Fuzzy logic control (FLC) system is a control system which is working based on error input data, rate of error, and accelaret of error of controlling variable. Using some rules of FAM (Fuzzy Associate Memory) which is constructed for resulting a decision can be used to actuator of controller. This paper is des-cribing about designing fuzzy logic as a control system for ship maneuvering, which is input for FLC are yaw error, yaw rate, and tracking error while the output of fuzzy logic control is command rudder signal. FLC con-sists of two units of controller; it is first controller unit work for autopilot and second controller unit for offset track. Interference function for FLC is Sugeno – Takagi which represent mathematic equation from input vari-able of FLC. Gain control of FLC based on least square estimation of error yaw, yaw rate, and output control signal relationship from LQR/LTR as a model reference control. Dynamic model of ship maneuvering has been derived on 3 dof with Clarke hydrodynamic coefficient. The capability of logic fuzzy control has been shown on simulation, for tanker ship model without interference or within interference. Robust of fuzzy logic control has been got from trajectory convergence error of yaw and yaw rate error when on turning simulation or off turning simulation toward the sector (0, 0).